Tillandsia‐Inspired Hygroscopic Photothermal Organogels for Efficient Atmospheric Water Harvesting. (26th August 2020) - Ni, Feng; Qiu, Nianxiang; Xiao, Peng; Zhang, Chang; Jian, Yukun; Liang, Yun; Xie, Weiping; Yan, Luke; Chen, Tao
Abstract: Tillandsia species with degenerated roots have evolved into hygroscopic leaves that absorb moisture from air. This interesting biological adaptability has inspired us to develop an integrated hygroscopic photothermal organogel (POG) to achieve a solar‐powered atmospheric water harvesting (AWH). The well‐designed hydrophilic co‐polymeric skeleton is fabricated to accommodate hygroscopic glycerin medium, which enables the POG self‐contained property, mechanically flexibility and synergistic enhancement of moisture sorption. The integration of interpenetrated photothermal component of poly‐pyrrole‐dopamine (P‐Py‐DA) can endow the POG an efficient solar‐to‐thermal property for controllable solar‐driven interfacial water releasing. The integrated POG has an equilibrium moisture sorption of 16.01 kg m −2 at the RH of 90 %, and daily water production as high as 2.43 kg m −2  day −1 is achieved in actual outdoor experiments. Abstract : Tillandsia‐inspired hygroscopic photothermal organogel (POG) is developed to realize atmospheric water harvesting. The combination of designable hydrophilic co‐polymeric skeleton, hygroscopic liquid medium, and photothermic component endows POG continuous, high‐efficient moisture sorption and effective solar‐heating water releasing.